1997
DOI: 10.1111/j.1365-2443.1997.119gc0317.x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of a Purkinje cell‐specific gene through a functional interaction between RORα and RAR

Abstract: Background: The orphan nuclear receptor RORa is highly expressed in the Purkinje cells of the cerebellum during the postnatal development of brain. A recent observation has been made that the RORa gene is disrupted in staggerer mice-which show a cell-autonomous defect in the development of the Purkinje cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…RORa in the SCN or other brain regions is a retinoid-related orphan receptor recently incorporated to the molecular clock machinery (Sato et al, 2004), which activates BMAL1 transcription in a 24-h cycle. It has been shown that RORa-mediated transcription is activated synergistically by RAR in Pukinje cerebellar cells (Matsui, 1997), evidencing a functional interaction between RORa and RAR transcription factors. RARs operate as heterodimers with RXRs (Soprano et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…RORa in the SCN or other brain regions is a retinoid-related orphan receptor recently incorporated to the molecular clock machinery (Sato et al, 2004), which activates BMAL1 transcription in a 24-h cycle. It has been shown that RORa-mediated transcription is activated synergistically by RAR in Pukinje cerebellar cells (Matsui, 1997), evidencing a functional interaction between RORa and RAR transcription factors. RARs operate as heterodimers with RXRs (Soprano et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The suppression of ROR␣ by LXR␣ was also seen when a synthetic tk-Pcp2/RORELuc reporter was used. This reporter contains three copies of RORE derived from the Pcp2 gene (Matsui, 1997). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…ROREx5-tk-LUC containing five copies of RORE (TATATCAAGGT-CAT) was cloned into pTKLuc as described by Medvedev et al (24). mPCP-2x4-tk-LUC containing four copies of mouse Pcp-2 RORE (GT-TATAGTAACTGGGTCAGGGGACT) was cloned into pTKLuc as described by Matsui (25). The inserted sequences in the TKLuc clones were confirmed by big dye terminator version 3.1 cycle sequencing (ABI, Foster City, CA).…”
Section: Methodsmentioning
confidence: 99%